Օժիտը և ամուսնական ունեցվածքի բաժանումը Կիլիկյան Հայաստանի իրավական փաստաթղթերում և առօրեականության մեջ - Գևորգյան, Զոհրաբ (Մատենադարան)
The dowry and the issue of marital property are components characterizing the culture of medieval everyday life and marital law, which are expressed in various ways in both medieval European (Roman law, Magna Carta, the Assizes of Antioch and Jerusalem in the Crusader States) and Oriental legal systems. In this case, we are talking about the circumstances conditioned by feudal relations of the High Middle Ages, where the role of private property, including marital property, had become more important over time in both legal documents and codes, and in everyday life. Marriage, as a legal institution, had also played an important role in the culture of Cilician Armenia. Проблема приданого и семейной собственности характеризуют культуру сосуществования в средневековой повседневной жизни и брачное право, которые по-разному выражаются в европейских и в восточных правовых отношениях. В данном случае речь идет об обстоятельствах, обусловленных феодальными отношениями развитого средневековья, где роль частной, в том числе семейной собственности со временем стала более заметной как в юридических документах и кодексах, так и в повседневной жизни. Брак, как правовой институт, также сыграл важную роль в культуре Киликийской Армении.
Keywords: Իրավունք